ICT’s Benefits and Challenges in EFL Classroom: A Systematic Review of the Literature from 2017 to 2023 - Noviyanti, Eka; Stefani, Oei; Songidah; Kulsum, Umi (UM Purwokerto Press, 2025)
Information Communication Technology (ICT) has become a significant aspect of teaching English as a Foreign Language (EFL) worldwide, including Indonesia.. This paper aims to investigate both the benefits and difficulties associated with using ICT in Indonesian EFL classrooms and explore ways to better prepare teachers to integrate ICT into their language instruction. The use of ICT in EFL teaching has been advantageous, particularly in enhancing classroom interaction and diversifying educational resources. This significance spurred the researchers to examine existing literature on ICT in English classrooms, both within Indonesia and internationally. A comprehensive literature review covering 2017 to 2023 was conducted, sourcing data from electronic databases such as SCOPUS, Semantic Scholar, Scimago, ERIC, ELICIT, Dialnet, and Google Scholar. Twenty selected studies were analyzed following the systematic review methodology outlined by Gough and Newman (year). The findings highlight several advantages of ICT in education. One key benefit is that it allows students to be more actively engaged and take on more significant roles in their learning experiences. However, there are notable challenges in implementing ICT, especially in regions with poor connectivity, like rural areas. From the students' perspective, some lack the necessary communication tools to participate fully in ICT-supported teaching and learning activities. On the teachers' side, one of the primary obstacles is the lack of adequate training and access to the necessary technological devices.